RANCANG BANGUN SISTEM PENGAMBILAN KEPUTUSAN PEMILIHAN BEASISWA PADA SMP 4 PSKD JAKARTA SELATAN - Dwi Yulistyanti (Sekolah Tinggi Teknologi Informasi NIIT, 2020)
Decision support system (DSS) the election of receiver scholarship only use Simple Additive Weighting (SAW) method for application of the calculation, no discuss other methods. for determine election of receiver scholarship at Junior High School PSKD 4 jakarta appropriate with criteria who gaves. the criteria involve rating, income parents of month, total of certificate, burden of parents. For support election of receiver scholarship then the method of research to use is Simple Additive Weighting (SAW), where every criterion gives rating factor. after researcher did research that Simple Additive Weighting (SAW) method that process can gives output rating who has one system who can gives rating at every student from listing result them get. Result of research was there thing device who make with progaming language Java Netbeans and the storage at database MYSQL can give smoothness in processing decision support system the election of receiver scholarship at junior high scholl PSKD 4 based on java and this research also can do rating alternative from result calculation weight of value student with use Simple Additive Weighting (SAW) method.